1969
DOI: 10.1029/jb074i012p03095
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the Pacific upper mantle

Abstract: Seismic refraction measurements of the compressional wave velocity of the upper mantle, obtained in the northeast Pacific Ocean between California and Hawaii, have shown a dependence on direction indicating anisotropy of velocity with a maximum of 8.6 km/sec in a roughly easterly direction and a minimum of 8.0 km/sec. In order to test whether or not these observations represent true anisotropy, rather than geographical variation of velocity, special anisotropy experiments were conducted at two locations center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
196
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(207 citation statements)
references
References 7 publications
11
196
0
Order By: Relevance
“…Raitt et al, 1969;Forsyth, 1975;Nataf et al, 1984;Tanimoto and Anderson, 1985;Shearer and Orcutt, 1986;Montagner and Tanimoto, 1990;Silver and Chan, 1991) and laboratory experiments (e.g. Carter and Avé Lallemant, 1970;Nicolas et al, 1973;Kunze and Avé Lallemant, 1981;Chopra and Paterson, 1981;Zeuch and Green, 1984;Zhang and Karato, 1995;Tommasi et al, 1999;Zhang et al, 2000;Bystricky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Raitt et al, 1969;Forsyth, 1975;Nataf et al, 1984;Tanimoto and Anderson, 1985;Shearer and Orcutt, 1986;Montagner and Tanimoto, 1990;Silver and Chan, 1991) and laboratory experiments (e.g. Carter and Avé Lallemant, 1970;Nicolas et al, 1973;Kunze and Avé Lallemant, 1981;Chopra and Paterson, 1981;Zeuch and Green, 1984;Zhang and Karato, 1995;Tommasi et al, 1999;Zhang et al, 2000;Bystricky et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Raitt et al (1969) and Morris et al (1969) have shown that the Pacific mantle immediately beneath the Moho is anisotropic.…”
mentioning
confidence: 99%
“…Upper mantle anisotropy of the Eastern Pacific was first observed by HESS (1964), RAITT et al (1969), andMORRIS et al (1969). They found the direction of maximum seismic velocity is perpendicular to the ridge axis .…”
Section: Seismic Anisotropy Of Upper Mantle and Stress Regime Within mentioning
confidence: 99%